ANALISIS LAYANAN PURNA JUAL TERHADAP KEPUASAN PELANGGAN ALAT BERAT KOBELCO CABANG BANJARMASIN - Makhfida Iswari; Nuril Huda (JWM (JURNAL WAWASAN MANAJEMEN), 2016)
Downturn in unit sales of heavy equipment nationwide since 2011 to 2015, also experienced by PT. Daya Kobelco CMI Branch of Banjarmasin, South Kalimantan. One of the company’s efforts to maintain unit sales are expected to improve after sales service that will satisfy the customers to keep buying the unit Kobelco. Based on the background of the problem this study aims to examine the effect of aftersales service to customersatisfaction. The quantitative research approach, with multiple linear regression analysis (Multiple rergression analysis). The study population is the entire customer (customer) who has made a purchase Kobelco unit at least three times in PT. DKCMI Branch of Banjarmasin, South Kalimantan, by using Slovin formula is obtained sample 175 respondents, the sampling method using accidental sampling. A number of tests performed, test the research instrument through validity and reliability test, then test the classical assumption (normality test, multicollinearity, and heteroscedasticity) . And then to test the significance of intervariable effect of using uji F and uji t. Results penilitian concluded, Sales Service Customer Satisfaction influence on aftersales service PT. Daya Kobelco CMI Branch Banjarmasin